Pengaruh Pertumbuhan Laba Dan Mekanisme Good Corporate Governance Terhadap Kualitas Laba - Keri Boru Hotang; Egi Ronauli Sinambela; Anisa Putri Nur Fatimah (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
Manufacturing is one of the sectors of the company that has an important role in supporting the economic growth of a country, has the main activity of managing raw materials or raw materials so that they become finished goods and then sell them to consumers. This study aims to obtain empirical evidence about the effect of earnings growth and good corporate governance mechanisms on earnings quality using five independent variables, namely earnings growth (PL), independent commissioners (KOMIND), audit committees (KA), managerial ownership (KM), institutional ownership (KI) and the dependent variable, earnings quality (KL). The sampling technique used is purposive sampling. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 totaling 174 companies. The sample in this study were 26 (twenty six) manufacturing companies. The data analysis technique used in this study is multiple linear regression analysis. The results of multiple linear regression analysis showed that managerial ownership and institutional ownership had no effect on earnings quality while earnings growth variables, independent commissioners and audit committees had a positive effect on earnings quality.